看顾自然: 从事实到价值，从尊敬到尊崇 - Rolston, Holmes, 1932-2025, author; Taiwan Ecological Stewardship Association, publisher (Colorado State University. Libraries, 2007)
Despite the classical prohibition of moving from fact to value, encounter with the biodiversity and plenitude of being in evolutionary natural history moves us to respect life, even to reverence it. Darwinian accounts are value-laden and necessary for understanding life at the same time that Darwinian theory fails to provide sufficient cause for the historically developing diversity and increasing complexity on Earth. Earth is a providing ground; matter and energy on Earth support life, but distinctive to life is information coded in the genetic molecules that superintends this matter-energy. Life is generated and regenerated in struggle, persists in its perishing. Such life is also a gift; nature is grace. Biologists and theologians join in celebrating and conserving the genesis on Earth, awed in their encounter with this creativity that characterizes our home planet.
Caring for nature: from fact to value, from respect to reverence
Kan gu zi ran :cong shi shi dao jia zhi, cong zun jing dao zun chong
Translated by Chen, Tzu-Mei; original English version in Zygon: Journal of Religion and Science 39 (2004).
Text in Chinese.
Keywords: nature as grace; genetic information; value distinction; fact distinction; evolutionary natural history; environmental conservation; order versus contingency; respect for nature; reverence for nature